The Contribution of Social Skills and Peer Attachment to the Subjective Well-Being of Adolescents with Dayak Ethnic Backgrounds in West Borneo - Ardila, Mutiara Reynissa; Nirwana, Herman (International Journal of Applied Counseling and Social Sciences, 2023)
Ideally, this research is motivated by the problems that exist in adolescents related to happiness in life they experience. Social skills and peer attachment are factors that affect the subjective well-being of adolescents. This study aims to determine how big the contribution of social skills and peer attachment to the subjective well-being of adolescents with Dayak ethnic background. The research method used is quantitative with descriptive correlational type. The study population was all students of class X, XI and XII at SMA Negeri 2 Sanggau located in Sanggau Regency with various cultural backgrounds. The research sample amounted to 125 people, who were selected by purposive random sampling technique, namely sampling by determining the criteria for a Dayak cultural background. The instrument used is a checklist with a Likert model scale. Data were analyzed by descriptive statistics, simple regression, and multiple regression. The research findings show that: (1) subjective well-being of adolescents is 75.2% in the high category, (2) on average 73.6% social skills are in the high category, (3) adolescent peer attachment shows high results with an average of 64.8%, (4) social skills have a fairly strong contribution to the subjective well-being of adolescents by 58.3%, (5) the contribution of peer attachment to subjective well-being of adolescents is 30.8 %, and (6) the contribution of social skills and peer attachment to subjective well-being is quite high at 69.4%. Happiness in life in adolescents is not only measured based on social skills and peer attachment to subjective well-being, which means that adolescents are able to express themselves in socializing well so that social skills have a large contribution to life satisfaction.